Molecular characterization of Leptospira sp by multilocus variable number tandem repeat analysis (MLVA) from clinical samples: a case report. (August 2015) - Pailhoriès, Hélène; Buzelé, Rodolphe; Picardeau, Mathieu; Robert, Sylvie; Mercier, Emmanuelle; Mereghetti, Laurent; Lanotte, Philippe
Highlights: The diagnosis of leptospirosis was made post-mortem in a man returning from Thailand. The Leptospira sp genotype was characterized by variable number tandem repeat (VNTR) analysis directly from clinical samples. This genotype has not yet been described with this method. This illustrates the diversity or the misreading of Leptospira sp strains from tropical climates. VNTR analysis directly on clinical samples is a reliable and rapid method. Summary: Leptospirosis is a zoonotic infection for which diagnosis is difficult. It has appeared as a global emerging infectious disease over recent years. Genotype determination often requires a Leptospira strain obtained by culture, which is a long and fastidious technique. A method based on multilocus variable number tandem repeat analysis (MLVA) to determine the genotype of Leptospira interrogans, performed directly on blood or urine samples, is proposed. This method was applied to a fatal case of leptospirosis for which the geographical origin of infection was unknown. This technique will allow a genotype to be obtained for L. interrogans, even when cultures remain negative.